Fizikalni eksperimenti 3: Zbirka laboratorijskih vaj - Repnik, Robert; Hauko, Robert (University of Maribor Press, 2022)
Physics Experiments 3: Collection of Laboratory Exercises. Physics experiments 3 - a collection of laboratory exercises - are intended for students of the 1st level of study programs Physics and Subject Teacher at the Faculty of Natural Sciences and Mathematics, University of Maribor. Laboratory exercises are conducted within the course Physics Experiments 3. The collection covers material in the field of oscillations and waves: Focal lengths of lenses, Deflection and interference, Stefan’s law, Coupled oscillation, Ultrasound speed, Friction oscillation, Resonance, Standing waves, Frequency and speed of sound, Interrupted pendulum, Spectrometer. The instructions are intended for the successful implementation of measurements, analysis, interpretation and evaluation of measurement results. The titles of independent projects that have been implemented within the course in previous years are added.